Tiga Lapis Makna Puisi ‘Aku Berkaca’ Karya Chairil Anwar - Bhanu Viktorahadi (Parahyangan Catholic University, 2020)
Interpretation is the art of seeking meaning just as the author originally intend- ed. In the process, the author’s intent becomes the key of which among many towards an interpretation. Each interpretation requires the interpreter to enter the author’s mind and identify with the author, achieve total experience or repeat the global experience of the author and enter the realm of his emotions. Chairil Anwar’s ‘aku Berkaca’ is an interesting text offering a rich depth of meaning to be drawn from. There are at least three layers of meaning contained within the poem, namely the context layer, the sound layer, and the meaning layer. These three layers of meaning usher the reader towards the climax indeed the climax as the author intends is a message and meaning in of itself.